The changing constitution - Jowell, Jeffrey (Oxford university press., 2005)
Since its first edition in 1985, The Changing Constitution has cemented its reputation for providing concise, scholarly and thought-provoking essays on the key issues surrounding the UK's constitutional development, and the current debates around reform. The ninth edition of this highly successful volume is published at a time of accelerated constitutional change. This collection of essays brings together fourteen expert contributors to offer an invaluable source of material and analysis for all students of constitutional law and politics. It clarifies the scope of the powers exercised by central, devolved and local governments within the UK, and the relationship between Britain, the EU and other regional and international legal systems